Reading reconsidered : a practical guide to rigorous literacy instruction - Lemov, Doug, 1967-; Driggs, Colleen; Woolway, Erica, 1979- (Jossey-Bass & Pfeiffer Imprints, Wiley, 2016)
"In the 2010 article "Building a Better Teacher"--the article that "launched" Teach Like a Champion, journalist Elizabeth Green compared two schools of thought--one that teaching skills were the most important driver of classroom learning, the other that content knowledge was the true driver. Some readers saw a conflict between these two perspectives. The authors of Reading Reconsidered have always thought that the answer was more complex: that technique was irreplaceable and helped teachers maximize the application of their subject knowledge but there was also no substitute for content knowledge. Moreover, they believed, there were in fact techniques specific to each of the content areas that drive results and could be delineated and learned like the general techniques in Teach Like a Champion. Reading Reconsidered is the authors' first effort to take on the challenge of defining subject specific methods. It is an anxious time for many teachers but also a time of great opportunity. This book will provide a road map from confusion to success"--